A Survey and Analysis of Process Modeling Languages - Zamli, Kamal Zuhairi; Mat Isa, Nor Ashidi (Malaysian Journal of Computer Science, 2004)
Process Modeling Languages (PMLs) are languages used to express software process models. Process Centered Software Engineering Environments (PSEEs) are the environments used to define, modify, analyse, and enact a process model. While both PMLs and PSEEs are equally important, it is the characteristics of PMLs that are the focus of this article. Over the past 15 years, there have been many PMLs (and PSEEs) developed. Despite many potential advances, the use of PMLs in industry has not been widespread. As PMLs could form a vital feature for future software engineering environments, it is useful to reflect on the current achievements and shortcomings, and to identify potential areas of omission. It is also useful to explore issues emerging from related research areas, the adoption of which could improve the applicability and acceptance of PMLs. Given such potential benefits, this paper presents a critical analysis of existing PMLs identifying each language’s strong points and weaknesses, thereby forming guidelines for the future design of PMLs.